2016
DOI: 10.3791/53449
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Resistance Training Improves Strength in Eight Weeks in Individuals with Multiple Sclerosis

Abstract: Hip weakness is a common symptom affecting walking ability in people with multiple sclerosis (MS). It is known that resistance strength training (RST) can improve strength in individuals with MS, however; it remains unclear the duration of RST that is needed to make strength gains and how to adapt hip strengthening exercises for individuals of varying strength using only resistance bands. This paper describes the methodology to set up and implement an adapted resistance strength training program, using resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Participants in both groups were instructed to complete 30 minutes of endurance training (eg, cycling, treadmill, or overground walking) 2 times per week and a lower extremity strength training program using resistance bands 3 times per week for 8 weeks. Strength training focused on lower extremity muscles (hip flexion, extension and abduction, and knee flexion and extension) using resistance bands, following the methods of Keller et al 29 All participants were assigned 2 functional exercises to complete each week (see Supplemental Digital Content 2C, available at: http://links.lww. com/JNPT/A294, which describes the functional exercises).…”
Section: Testing Sessions At Baseline Visit 1 Participantsmentioning
confidence: 99%
“…Participants in both groups were instructed to complete 30 minutes of endurance training (eg, cycling, treadmill, or overground walking) 2 times per week and a lower extremity strength training program using resistance bands 3 times per week for 8 weeks. Strength training focused on lower extremity muscles (hip flexion, extension and abduction, and knee flexion and extension) using resistance bands, following the methods of Keller et al 29 All participants were assigned 2 functional exercises to complete each week (see Supplemental Digital Content 2C, available at: http://links.lww. com/JNPT/A294, which describes the functional exercises).…”
Section: Testing Sessions At Baseline Visit 1 Participantsmentioning
confidence: 99%
“…Future studies should examine pain, cognition, and quality of life measures in combination with more commonly-measured motor impairments (e.g., strength). We have previously shown that quantitative strength, balance, and walking measures are useful for assessing function in MS (Fritz, 2015a, 2015b) and are amenable to rehabilitation (Keller, 2016). Rehabilitation can impact quality of life, pain, and cognition; given the results of this study, future work should also examine structural brain changes that might accompany these behavioral improvements.…”
Section: Discussionmentioning
confidence: 99%
“…21 • In managing weakness, our study showed that significant improvements can be made in as little as 8 weeks using resistance strength training. 22 Endurance training has also been effective in strength improvement 23 ; however, the dose and intensity required to achieve the most optimal gains remain unclear.…”
Section: Strengthmentioning
confidence: 99%